Measurement of the prevalence of intervention/complication in puerperal women attending a university hospital during the pandemic of COVID-19 by the maternity safety thermometer - Vitor Leonardo Nandi; Roxana Knobel; Jéssica Goedert Pereira; Mariana Nunes Miranda Carasek da Rocha; Yasmin Lima Gouveia Arruda; Alberto Trapani Junior; Marie Margot Martin (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: measuring the prevalence of interventions and/or complications based on the Maternity Safety Thermometer (MST) criteria and verifying associations with sociodemographic, clinical, and obstetric factors. Methods: prospective observational study conducted with postpartum women admitted to the maternity ward of a tertiary hospital, from October 10th to December 30th, 2020. Data were collected from medical records and self-administered questionnaires from 260 patients. Results: harm-free care was detected in 17.7% of participants, 66.9% had low-temperature damage (one or less intervention/complication) and 33.1% of patients had elevated temperature damage (two or more intervention/complication). The most frequent intervention was the "scar", given that 38.5% had abdominal scarring (cesarean section) and 26.5% had perineal scarring (2nd-degree tear or greater - spontaneous or by episiotomy). The second most frequent MST item was related to the perception of safety (30%), followed by complications to the newborn (12.3%), infection (11.2%), and hemorrhage (9.2%). Factors related to high temperature were: being of social class A or B, having a previous cesarean section, and being hospitalized during pregnancy. Conclusions: one-third of the participating women had two or more complications/interventions (high temperature by the MST), factors that are related to this temperature were: being of social class A or B, having a previous cesarean section, and being hospitalized during pregnancy.